Empowering the elderly to promote active ageing in the labour market: a new strategic scheme to improve ageing human resource and to solve shortage of labour force in Taiwan - Soong, Jenn-Jaw (Penerbit Universiti Kebangsaan Malaysia, 2020)
Ageing and elderly poverty have now become a general phenomenon that is influencing population structure and economic development worldwide as well as having a great impact in particular on dependency ratio and the labour market. One of the countries that is experiencing a sharp increase in its ageing population is Taiwan, and consequently, this has heavily affected the country’s economy and labour force market. In Taiwan, there is almost a quarter century of life span for the ageing after 60, and thus it is crucial for the ageing to learn and plan a better life in the final stage in order to continue with their life productively and independently. As the elderly are now living longer, they must be able to work longer in order to maintain financial independence in their old age. Hence, faced with longevity of life and better health, it becomes a requisite for the government to empower active ageing in Taiwan’s labour market. An alternative and creative career reconstruction for the ageing can be arranged by combining work contribution, volunteering assistance, and learning for pleasure. Simply put, turning elderly burden into an active work force should become an important ageing policy in Taiwan.